The scope of comparative literary studies: review of schools of study - Yaacob, Adli (2011)
This paper provides a description of the development of the ‘Study of Comparative Literature’; its naming, origins, schools of study, and scope of study. From its inception, Comparative Literature ‘ what is’ Comparative Literature and its study has been a matter of question, from inside the earliest schools of study in France and beyond its borders. De Certeau’s “Practice Theory” has been employed seeking to resolve the cultural and linguistic differences in the name of the field, as well as the subject of study. Then, the social and theoretical influences which differentiate the dominant French and rivaling American schools of Comparative Literature are outlined. These serve as a background for the introduction of Post-Colonial Studies. Examples of the expanding range of studies in Comparative Literature are presented, including remarks of their ‘acceptedness’ as Comparative Literature, or not .